Factors Associated with the Presence of Extended-Spectrum Beta-Lactamase-Producing Pathogens in Urinary Tract Infections in a Private Clinic in Lima, Peru (2020)
Introduction: Urinary tract infections (UTIs) are the second most frequent reason for healthcare visits, and antibiotic resistance among gram-negative bacteria of the Enterobacteriaceae family has increased significantly worldwide. The emergence of microorganisms that produce extended-spectrum beta-lactamase (ESBL) is especially problematic. This study aims to identify factors associated with the presence of UTI caused by ESBL-producing pathogens. Material and methods: An analytical cross-sectional study was conducted, and the urine culture database from a private healthcare clinic was analyzed. Factors possibly associated with the appearance of UTIs due to ESBL-producing pathogens were analyzed, including sex, age, number of hospitalizations, and previous UTIs. Results: A total of 1405 positive urine cultures were studied, 85.48% of which belonged to women. The mean age of the subjects was 39.98 ± 24.51 years, 24.13% of whom were over 60 years old. Of these, 55.56% had been attended on an outpatient basis. Almost half (49.18%) of the cultures tested positive for ESBL-related UTI, 96.58% of which had not presented with a previous UTI. A statistically significant association was found between sex and the development of UTI caused by ESBL-producing microorganisms (p = 0.007), with the male sex having the highest association (prevalence ratio, 1.224; 95% confidence interval: 1.035-1.448). In addition, age, number of previous hospitalizations, and prior intensive care unit admissions also showed associations with UTI development. No association was found with the presence of previous UTIs. Conclusion: A high frequency of UTIs were ESBL-related, and the factors associated with ESBL-related UTIs were male sex, age >60, and previous hospitalizations.